Neural functions in cancer: Data analyses and database construction - Tan, Renbo; Wang, Feilong; Zhou, Yi; Huang, Zhenyu; An, Zheng; Xu, Ying (Frontiers in Genetics, 2023)
Recent studies have revealed that neural functions are involved in possibly every aspect of a cancer development, serving as bridges connecting microenvironmental stressors, activities of intracellular subsystems, and cell survival. Elucidation of the functional roles played by the neural system could provide the missing links in developing a systems-level understanding of cancer biology. However, the existing information is highly fragmented and scattered across the literature and internet databases, making it difficult for cancer researchers to use. We have conducted computational analyses of transcriptomic data of cancer tissues in TCGA and tissues of healthy organs in GTEx, aiming to demonstrate how the functional roles by the neural genes could be derived and what nonneural functions they are associated with, across different stages of 26 cancer types. Several novel discoveries are made, including (i) the expressions of certain neural genes can predict the prognosis of a cancer patient; (ii) cancer metastasis tends to involve specific neural functions; (iii) cancers of low survival rates involve more neural interactions than those with high survival rates; (iv) more malignant cancers involve more complex neural functions; and (v) neural functions are probably induced to alleviate stresses and help the associated cancer cells to survive. A database, called NGC, is developed for organizing such derived neural functions and associations, along with gene expressions and functional annotations collected from public databases, aiming to provide an integrated and publicly available information resource to enable cancer researchers to take full advantage of the relevant information in their research, facilitated by tools provided by NGC.